New insights into oxidative-reductive leaching of chalcopyrite concentrate using a central composite factorial design - Rissoni Toledo, Ailton Guilherme [UNESP]; Tayar, Samir Prioto [UNESP]; Arena, Fabiana Antonia [UNESP]; Benedetti, Assis Vicente [UNESP]; Bevilaqua, Denise [UNESP] (Elsevier, 2022)
A response surface capable of describing the extraction of copper with high statistical confidence (R2 = 0.9973) was obtained using a central composite factorial design (CCD). The parameters used were the initial concentration of Fe2+ ions ([Fe2+]i) and pulp density (ρpulp). The results evidenced that chalcopyrite leaching was strongly influenced by the solution potential, which was a function of the [Fe2+]i:ρpulp ratio. The optimal parameters obtained for maximizing the copper extraction percentage were those that satisfied a [Fe2+]i:ρpulp ratio of ≈ 80 (mmol L−1/%), in the range from 200 to 398 mmol L−1 of Fe2+. The [Fe2+]i:ρpulp ratio of ≈ 80 allowed an optimal range of solution potential for most of the experiment duration, which provided a copper extraction of 91 ± 3% in 28 days, under moderate conditions. The leaching residues were analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES), X-ray diffractometry (XRD), and scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS). The mathematical model, together with the calculated Nernst potentials of the main oxidation–reduction reactions of chalcopyrite, indicated that the copper extraction was governed by experimental conditions that favored chalcopyrite reduction coupled with the chalcocite oxidation reaction. Hypotheses to explain the reasons for certain experimental conditions that could increase or decrease chalcopyrite dissolution were formulated and are extensively discussed. These findings contribute to the development of new routes for the processing of chalcopyrite mineral.
Keywords: Chalcopyrite; Dissolution optimization; Leaching; Redox potential; Response surface